Sanggenon C Stimulates Osteoblastic Proliferation and Differentiation, Inhibits Osteoclastic Resorption, and Ameliorates Prednisone-Induced Osteoporosis in Zebrafish Model - Huijuan Wang; Tingting Feng; Donggui Guo; Min Zhang; Lin Chen; Ying Zhou (Molecules, 2018)
Sanggenon C (SC), which is a natural flavonoid found in the stem bark of Cortex Mori, has been discovered to have the antioxidant, anti-inflammatory, and antitumor properties. However, its effect in osteoporosis has not yet been reported. In this research, the effect of SC on the proliferation of MC3T3-E1 cells was evaluated by using the MTT assay. Alkaline phosphatase (ALP) activity and the mRNA expression of Runx2, Collagen I, OPG, and RANKL were examined. TRAP-positive cell counting and bone resorption pits were adopted to observe the effect of SC on the formation and function of osteoclasts. Next, the mRNA level of TRAP, CTSK, NFATc1, and TRAF6 of osteoclasts were measured by real-time qPCR. In addition, the anti-osteoporosis activity of SC in vivo was evaluated in the zebrafish model. Our study indicated that SC exhibited a significant stimulatory effect on MC3T3-E1 cell proliferation at 1 to 10 μM and caused an increase in ALP activity at 0.3 to 10 μM. It could upregulate the expression of Runx2, Collagen I, and increases the OPG/RANKL ratio. Furthermore, SC was found to inhibit the formation and function of osteoclasts, which is demonstrated by a lower number of TRAP-positive multinuclear cells and a fewer area of bone resorption pits compared to the control group. TRAP, CTSK, and NFATc1 were downregulated in 0.3 to 10 μM SC treated groups. In addition, 3 to 10 μM SC also inhibited the expression of TRAF6 mRNA. When prednisone-induced zebrafish was treated with 0.3, 1, 3, and 10 μM SC, higher mineralization of vertebrate column was discovered in a dose-dependent pattern, which suggests that SC could reverse the bone loss of zebrafish caused by prednisone. In summary, these findings indicated that SC has the potential to prevent or treat osteoporosis.